The Influence of K3 (Occupational Health and Safety), Training and Career Development on the Performance of PTPN IV Kebun Gunung Bayu Employees - Tiur Novrita Marpaung; Nana Dyki Dirbawanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Indonesian palm oil industry is important for the Indonesian economy with palm oil trade performance continuing to increase. However, the challenge of developing oil palm is limited human resources. Companies implement K3 because many activities involve work accidents and disease risks. Training to provide, and develop competencies. Career development is company support to motivate employees to be able to develop their careers better. This research aims to analyze the influence of K3, training and career development on the performance of PTPN IV Kebun Gunung Bayu employees. The research method is quantitative. Data analysis methods are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that K3, training and career development have a significant effect on employee performance.